Associação entre transtornos mentais comuns, distúrbios do sono e sinais e sintomas menopáusicos: Pesquisa Saúde da Mulher 2015 - São Leopoldo/RS - Neutzling, Agnes Ludwig (Universidade do Vale do Rio dos Sinos, 2018)
Objective: To investigate the association of Common Mental Disorders (CMD) and sleep disorders with moderate/severe menopausal signs and symptoms in adult women in southern Brazil. Methods: A cross-sectional population-based study with a representative sample of 393 women (40-69 years) living in the urban area of São Leopoldo / RS. For data collection, a standardized and pre-tested questionnaire was used, containing: Self Reporting Questionnaire (SRQ-20) for the CMD (SRQ-20>7); Pittsburgh Sleep Quality Index (PSQI-BR) for sleep disorders (PSQI>5); and Menopause Rating Scale (MRS), for the outcome moderate/severe menopausal signs and symptoms (MRS>8). Prevalence ratios (PR), unadjusted and adjusted, and Confidence Intervals of 95% (95%CI) were estimated using robust Poisson regression. Results: The prevalence of moderate/severe complaints was 58.0% (95%CI 53.0-63.0), presence of CMD was 40.2% (95%CI 35.3-45.2) and sleep disorders was 49.4% (95%CI 44.3-54.5). CMD and sleep disorders simultaneously occurred in 34.4% (95%CI 29.6-39.3%). Women with CMD (p<0.001) and sleep disorders (p<0.001) had higher prevalences of the outcome. Presence of CMD and sleep disorders increased threefold the probability of outcome. After adjustment, CMD and sleep disorders maintained a strong association with moderate/severe menopausal complaints (p<0.001). Conclusions: There was a greater probability of moderate/severe signs and symptoms in women with CMD and sleep disorders. These evidences suggest that the quality of life of the sample may be affected. Considering the complex temporal relationship between TMC, sleep disorders and menopausal signs and symptoms, it is relevant to conduct longitudinal studies following women with such problems during TM, allowing the identification of temporality between exposures and outcome.
Keywords: Menopausa; Climatério; Sono; Privação de sono; Transtornos mentais; Menopause; Climacteric; Sleep; Sleep deprivation; Mental disorders; ACCNPQ::Ciências da Saúde::Saúde Coletiva